Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/cpp.2465
|View full text |Cite
|
Sign up to set email alerts
|

Predicting boundary violation propensity among mental health professionals

Abstract: Despite its clear importance, there have been very few empirical investigations of boundary violation propensity among mental health professionals. The present study explored the relationships between self-reported propensity for boundary violations and predictors theorized to increase their likelihood. Australian mental health professionals (N = 275) completed an online questionnaire battery including demographics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Papers selected for inclusion were published between 2013 and 2021 (see Table 3). The majority were completed in the United States, however, Australia (Dickeson et al, 2020), Germany (Clemens et al, 2021), and the United Kingdom (Ford et al, 2021) were represented.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Papers selected for inclusion were published between 2013 and 2021 (see Table 3). The majority were completed in the United States, however, Australia (Dickeson et al, 2020), Germany (Clemens et al, 2021), and the United Kingdom (Ford et al, 2021) were represented.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Completion rate in the studies ranged from 5% (Dickeson et al, 2020) to 95.97% (Howard et al, 2017).…”
Section: Acesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch Healthcare Inspectorate has, for instance, developed a brochure that advises healthcare organizations to develop SBV guidelines as part of a professionals’ employment contract [ 33 ]. Research into SBV has identified the psychological aspects of individual healthcare professionals that may lead to SBV [e.g., 34 ] and emphasis has been placed on individual responsibility to prevent SBV rather than on organizational responsibility [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normalizing conversations among professionals about sexuality and acknowledging inappropriate sexual feelings may prevent boundary violations, yet these conversations are challenging. A high prevalence of sexual and romantic attraction between professionals and clients has been reported, particularly in mental healthcare [ 2 , 34 , 43 ]. Talking about these sexual feelings and desires can help professionals to recognize and handle these feelings, but sexual desire and attraction to clients remains a taboo subject [ 44 ].…”
Section: Discussionmentioning
confidence: 99%